Peningkatan Kemampuan Pemecahan Masalah Melalui Model PBL pada Materi Pengurangan Kelas 3 SDN Kauman 1 - Putri Marhaeni, Aurila; Restian, Arina; Nur Kumalasari, Ratna (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the improvement of problem-solving skills in 3C grade students at SDN Kauman 1 through the implementation of the Problem-Based Learning (PBL) model on subtraction of whole numbers. The research employs a quantitative approach with a classroom action research (CAR) design conducted in two cycles. Data were collected through observation, diagnostic and formative assessment tests, interviews, and documentation. The findings reveal that the implementation of PBL enhances students' problem-solving skills, as evidenced by the increase in the average pre-test score from 55.32 to 78.46 in the post-test. Moreover, PBL positively influences students' interest and motivation in learning. The use of technology, visual media, and problem-based games creates an engaging, interactive, and relevant learning experience for students. The application of PBL involving group collaboration, peer teaching, and concrete media also strengthens students' understanding of the material. Overall, this study demonstrates that PBL is effective in improving the quality of mathematics learning in elementary schools.